CONTINUOUS PROFESSIONAL DEVELOPMENT OF JUNIOR HIGH SCHOOLS’ ISLAMIC RELIGIOUS EDUCATION TEACHERS AT BANDAR LAMPUNG CITY, INDONESIA - Robiyah, Siti; Koderi, Koderi; Muin, Juhri Abdul; Hijriyah, Umi (International Journal of Educational Management and Innovation, 2021)
The purpose of this study was to determine the continuous professional development which covers self-development, scientific publications, and innovative works on Islamic religious education teachers in Bandar Lampung city, Indonesia. This study employs the qualitative-descriptive approach with the teachers, principals, the chairperson of Islamic religious education Subject Teachers' Conference (MGMP), and the head of State Office of Education Bandar Lampung as the sources of data. The data collected through interviews, observations, and documentation. The data analysis techniques used were data triangulation through data reduction, data presentation, and conclusion drawing. This study discovers that 1) to develop themselves, the teachers join MGMP activities, training, workshops, seminars, and others, 2) for scientific publications in the form of scientific papers, the teachers participate in the national level competitions and workbooks writing although, in a minimal amount, 3) for innovative work, the teachers prepare the learning standards, learning guidelines, semester exam questions, syllabus development, lesson plan development, teaching materials development, editing blueprints of Islamic religious education questions although without continuous innovation. It recommended to foster self-development, scientific publications, and work innovation, PAI teachers in junior high schools should take part in training, seminars, and workshops, both independently and held by the education offices by taking into account good management theories, namely activities designed based on needs analysis, coordination with all institutions. The implementation of activities should have precise and measured outputs. An evaluation is also needed to find out whether the self-development, scientific publications, and innovative works have achieved or not.Â